(3cJGH (B( (3GdgfOi (B) (3aj GdMSGHs - (3TeS GdOjf eMeO Hf QHjY GdRQcTj GdegfOSs ((3jMji Hf Ydi Hf ESeGYjd Hf Ydi Hf YHO GdbGOQ s)
(3ChdgG (B:s
(3EYde QMefG hEjGc , Cf GdgfOi eHfi Ydi JSY UhQ gi gPg (B: 1(3, (B2(3, (B3(3, (B4(3, (B5(3, (B6(3, (B7(3, (B8(3, (B9(3, s
(3BNQgG (B:s
(3Je GdcJGH HYhf Gddg s
(3dYd GdeDda ef YdeGA GdbQf GdKGfi YTQs
(3jdjg MhGT Ydi gPG GdcJGH dYjT Hf CMeO Hf jhSas
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B76 s
Keywords: (3GdQjGVjGJs